2022
DOI: 10.18593/evid.30144
|View full text |Cite
|
Sign up to set email alerts
|

Demography and esterase polymorphism of brazilian populations of Zaprionus indianus (Diptera: Drosophilidae) from the Brazilian Cerrado localities

Abstract: Zaprionus indianus (fig fly) is a drosophilid of African origin that was recorded in Brazilian territory in 1999, quickly dispersing throughout the country, causing impacts on fig culture, and becoming one of the dominant Drosophilidae species in the Cerrado biome. Due to the fact it is an invasive species and a potential pest in fruit cultivars, it is essential to monitor the variations in the populations of this species aiming to verify its genetic and demographic structure and possible impacts on the drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…One of these species, Zaprionus indianus , native to Africa, was first recorded in Brazil in 1999 (Vilela, 1999), and recently another drosophilid (originally from Africa) species of the same genus, Zaprionus tuberculatus , was registered in the Americas in the Brazilian Cerrado (Cavalcanti et al., 2021). Since the invasion, the species has rapidly spread throughout the country (Commar et al., 2012; Rios et al., 2022) and has become a significant pest in fig crops, causing major economic impacts (Commar et al., 2012; Vieira et al., 2019; Vilela & Goñi, 2000). Other studies have shown that Z. indianus is detrimental to the cultivation of tomato, guava, mango, cherry, and blueberry (Bragard et al., 2022; Khaldi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these species, Zaprionus indianus , native to Africa, was first recorded in Brazil in 1999 (Vilela, 1999), and recently another drosophilid (originally from Africa) species of the same genus, Zaprionus tuberculatus , was registered in the Americas in the Brazilian Cerrado (Cavalcanti et al., 2021). Since the invasion, the species has rapidly spread throughout the country (Commar et al., 2012; Rios et al., 2022) and has become a significant pest in fig crops, causing major economic impacts (Commar et al., 2012; Vieira et al., 2019; Vilela & Goñi, 2000). Other studies have shown that Z. indianus is detrimental to the cultivation of tomato, guava, mango, cherry, and blueberry (Bragard et al., 2022; Khaldi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of these species, Zaprionus indianus, native to Africa, was first recorded in Brazil in 1999 (Vilela, 1999), and recently another drosophilid (originally from Africa) species of the same genus, Zaprionus tuberculatus, was registered in the Americas in the Brazilian Cerrado (Cavalcanti et al, 2021). Since the invasion, the species has rapidly spread throughout the country (Commar et al, 2012;Rios et al, 2022) and has become a significant pest in fig crops, causing major eco-…”
mentioning
confidence: 99%